2016
DOI: 10.1038/ni.3630
|View full text |Cite
|
Sign up to set email alerts
|

TET proteins regulate the lineage specification and TCR-mediated expansion of iNKT cells

Abstract: TET proteins oxidize 5-methylcytosine in DNA to 5-hydroxymethylcytosine and other oxidation products. We found that simultaneous deletion of Tet2 and Tet3 in mouse CD4+CD8+ double-positive thymocytes resulted in dysregulated development and proliferation of invariant natural killer T cells (iNKT cells). Tet2-Tet3 double-knockout (DKO) iNKT cells displayed pronounced skewing toward the NKT17 lineage, with increased DNA methylation and impaired expression of genes encoding the key lineage-specifying factors T-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
257
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(282 citation statements)
references
References 55 publications
23
257
2
Order By: Relevance
“…This is the case for Tet2 (and to a lesser degree Tet3), which is consistently reported in murine models [39,40,43,[45][46][47]49] and human cells [37,38,42,[50][51][52]. Of note, the role of Tet2 in mast cell differentiation described above [40] is partially independent of 5hmC, as rescuing mast cell developmental changes upon Tet2 knockout was only possible by the re-expression of Tet2 independently of its catalytic activity, which assumes that Tet2 possibly interacts with other complexes (something similar has been shown between TET1 and the SIN3A co-repressor complex [53]).…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodsupporting
confidence: 73%
See 2 more Smart Citations
“…This is the case for Tet2 (and to a lesser degree Tet3), which is consistently reported in murine models [39,40,43,[45][46][47]49] and human cells [37,38,42,[50][51][52]. Of note, the role of Tet2 in mast cell differentiation described above [40] is partially independent of 5hmC, as rescuing mast cell developmental changes upon Tet2 knockout was only possible by the re-expression of Tet2 independently of its catalytic activity, which assumes that Tet2 possibly interacts with other complexes (something similar has been shown between TET1 and the SIN3A co-repressor complex [53]).…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodsupporting
confidence: 73%
“…In line with this, 5hmC changes are overrepresented in highly transcribed genes. For example, chromatin-accessible-regions are associated with T cell [36,44] and induced natural killers (iNK) T cell development [45], Treg FoxP3 activation [46,47], B cell identity genes [39,41], or Bcl6 binding sites in T follicular helper (Tfh) cells [48] (Figure 2 and Table 1). During mast cell development, it was shown that Tet2 knockout caused differential 5hmC levels in genes enriched with leukocyte differentiation and proliferation, malignant transformation, and mast cell-related processes [40].…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…TET2 mutations can be present in T cells in CMML [35] and are frequent in cases with AID (Itzykson et al unpublished observation). TET enzymes have been involved in normal innate and adaptive immunity [36,37], but how TET2 mutations affect the function of normal T cells remains unclear.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…After deletion of Tet2 and Tet3 genes broadly in all T cells, a subset of innate-like and glycolipid-CD1d specific T cells called NKT cells displayed an altered differentiation pattern and were expanded and could transfer lymphoma-like disease [15•]. NKT subset specific transcription factor expression was altered in these mice and the population of NKT cells was biased to a normally rare RORγt-dependent subset called NKT17 [15•]. This phenotype was associated with reduced chromatin accessibility at distal regulatory elements that were normally enriched for 5hmC in wild-type NKT cells [15•].…”
Section: Tet Proteins During Natural Differentiationmentioning
confidence: 99%